2016
DOI: 10.1021/acs.jafc.6b02239
|View full text |Cite
|
Sign up to set email alerts
|

Cu-Chitosan Nanoparticle Mediated Sustainable Approach To Enhance Seedling Growth in Maize by Mobilizing Reserved Food

Abstract: Food crop seedlings often have susceptibility to various abiotic and biotic stresses. Therefore, in the present study, we investigated the impact of Cu-chitosan nanoparticles (NPs) on physiological and biochemical changes during maize seedling growth. Higher values of percent germination, shoot and root length, root number, seedling length, fresh and dry weight, and seed vigor index were obtained at 0.04-0.12% concentrations of Cu-chitosan NPs as compared to water, CuSO4, and bulk chitosan treatments. Cu-chito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(106 citation statements)
references
References 34 publications
9
95
0
2
Order By: Relevance
“…Chitosan-Cu nanonetwork is evident through a higher Cu accumulation in porous area which supports the ion-exchange resins and surface chelating mechanism [12]. Cu-chitosan nanocomposite has a weighty effect on plant cells as they easily pass into the seeds along with encapsulated Cu and participate strongly in the metabolism of germinating seeds [13]. These studies strongly hypothesize a cumulative effect of chitosan elicitors to induce defense enzymes and direct Cu ions toxicity towards fungi.…”
Section: Antifungal Activity Assaysupporting
confidence: 60%
See 1 more Smart Citation
“…Chitosan-Cu nanonetwork is evident through a higher Cu accumulation in porous area which supports the ion-exchange resins and surface chelating mechanism [12]. Cu-chitosan nanocomposite has a weighty effect on plant cells as they easily pass into the seeds along with encapsulated Cu and participate strongly in the metabolism of germinating seeds [13]. These studies strongly hypothesize a cumulative effect of chitosan elicitors to induce defense enzymes and direct Cu ions toxicity towards fungi.…”
Section: Antifungal Activity Assaysupporting
confidence: 60%
“…The improved antimicrobial activity of Cu NPs as compared to copper salt is due to their unique property, i.e., large surface area to volume ratio [9]. Recently, the investigations showed that incorporation of Cu NPs into chitosan matrice significantly enhanced its antimicrobial and antifungal activity [10][11][12][13]. The Cu@Chit NCs can combine the properties of biopolymer and nanosized copper; therefore, their application can be more effective than separately.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In addition, it was reported that Cu NPs were benecial to growth and nutriment accumulation of Vigna radiate and maize. 20,21 However, pure Cu NPs are easy to agglomerate, leading to decrease of antibacterial activity. 22 In order to address this problem, we are searching for a suitablybased material to reduce the agglomeration of Cu NPs.…”
Section: Introductionmentioning
confidence: 99%
“…The root length, straw height and seedling length of the wheat plants were measured and recorded daily. Seed vigor index (SVI) was calculated on day 10 using the following equation: SVI = [germination (%)] × [seedling length (cm)] . Fresh weights were measured respectively after 2 weeks of growth and dry weights were calculated according to the moisture contents which were determined by a moisture analyzer (MB23, Ohaus Corporation, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%